Эколого-паразитологическая характеристика моллюсков водоемов Килийской дельты Дуная - Черногоренко, М.И. (Вестник зоологии, 1969)
Ecological and parasitological investigations of mollusks from the basins of the Kiliyskaya delta of the Danube permit the peculiarities of distribution of the Trematoda larva forme to be determined in these basins. The amount of the Trematoda larvae in the delta arms and bays is very scanty. It is a result of hydrological and hydrobiological peculiarities of these basins (great depths, very muddy water, almost total absence of higher water plants, silt accumulations on the bottom, swift current in the arms) hindering here the propagation of the organisms in which these larvae develop. On the contrary, in the band of littoral vegetation the intermediate hosts of Trematoda are widely represented. That is why the Trematoda larvae are concentrated mainly here.
A great number of parasites is detected in flood-land basins of the delta. The helminths pathogenic for agricultural and industrial animals are found there.
When regulating the Danube discharge and creating the irrigation systems many of the helminths found here can be a serious threat for agricultural and industrial animals.